PENERAPAN PERMAINAN EDUKATIF UNTUK MENINGKATKAN PENGUASAAN MUFRADAT SISWA KELAS III SDI DATOK SULAIMAN PALOPO (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the use of educational game media by guessing word actions and composing sentences in improving students' vocabulary mastery and to determine the supporting and inhibiting factors in its implementation in grade III students of SDI Datok Sulaiman Palopo. The Classroom Action Research (CAR) method using the Kemmis and McTaggart model was implemented in two cycles with 21 students as subjects using the stages of planning, action, observation, and reflection. Data were collected through observation, interviews, documentation, and tests. The results showed a significant increase in students' listening skills, marked by an increase in the average score from 50.52% in the pre-cycle to 67.61% in the first cycle, and reaching 84.42% in the second cycle. The percentage of learning completion increased from 23.80% to 80.95%. Supporting factors include interesting learning media, student involvement, and teacher strategies, while inhibiting factors include the lack of use of Arabic outside the classroom and low student self-confidence.